Surface interactions of Fusarium graminearum on barley. (20th December 2017) - Imboden, Lori; Afton, Drew; Trail, Frances
Summary: The filamentous fungus Fusarium graminearum, a devastating pathogen of barley ( Hordeum vulgare L.), produces mycotoxins that pose a health hazard. To investigate the surface interactions of F. graminearum on barley, we focused on barley florets, as the most important infection site leading to grain contamination. The fungus interacted with silica‐accumulating cells (trichomes and silica/cork cell pairs) on the host surface. We identified variation in trichome‐type cells between two‐row and six‐row barley, and in the role of specific epidermal cells in the ingress of F. graminearum into barley florets. Prickle‐type trichomes functioned to trap conidia and were sites of fungal penetration. Infections of more mature florets supported the spread of hyphae into the vascular bundles, whereas younger florets did not show this spread. These differences related directly to the timing and location of increases in silica content during maturation. Focal accumulation of cellulose in infected paleae of two‐row and six‐row barley indicated that the response is in part linked to trichome type. Overall, silica‐accumulating epidermal cells had an expanded role in barley, serving to trap conidia, provide sites for fungal ingress and initiate resistance responses, suggesting a role for silica in pathogen establishment.